Perencanaan Transformasi Ternak Sapi Perah ke Wisata Edukasi Susu Segar di Jatirejo Semarang - Elizabeth Lucky Maretha Sitinjak; Laksmi Hartajanie; Lindayani; Florentinus Budi Setiawan; Shandy Jannifer Matitaputty (Servirisma, 2021)
The purpose of Community Service in Jatirejo Village, Gunungpati District, Semarang City is to help the Dairy Cattle Group (KTSP) in particular, to be able to transform from a simple livestock concept to a dairy cattle educational tourism area. At the beginning of the Covid-19 pandemic in 2020, the dairy cattle population increased by 0.53% nationally, but the dairy cattle population in Central Java decreased by 0.65% and production decreased by 2.94%. In 2021, there will be more demand for Dairy Cow Milk, because dairy milk is processed into fresh milk which has a very complete nutritional content, rich in protein, fat, carbohydrates, minerals, and vitamins. The nutritional content of milk is calcium, phosphorus, zinc, vitamins A, D, B12, B2, amino acids and pantothenic acid. There are several simple processing technologies that can be applied in the environment of farmers to preserve milk, including pasteurization and fermentation (yoghurt, yakult, and kefir). This processing method allows the shelf life to be extended and milk has different flavors and textures so that it can increase the selling value of the product. In addition, the place for milking cows and shops selling fresh milk and its products are designed to be instagramable. Transformation from dairy cow's milk into fresh milk with various processing, accompanied by the concept of marketing for cattle education tourism. The financial feasibility study supports the transformation of dairy cattle, with the concept of a milking place that is hygienic, environmentally friendly, and attracts millennials to drink fresh milk.